Role of Notary in Abroad and Indonesia - Haingo Rabanirajona (Jurnal Akta, 2020)
One of the important professions in society is notary. This profession is a special profession because it is a public official in carrying out its duties which is bound by juridical norms and professional code of ethics. The notary code of ethics becomes a moral principle determined by the Indonesian Notary Association (INI) which is the basis for organizing or regulating the notary professional code of ethics in relation to many parties, which of course must be obeyed or obeyed by every member who is bound or binds himself/herself in the association (organization) that. The consequences as a member of this profession must be understood by a notary, because sourced from here, the dignity of the profession can be maintained. The position of the Notary which is urgent in human life makes the process of someone who wants to become an expert notary public important. Therefore, in notarial education, notary ethics should also be considered. So in this case it is emphasized that a professional education without education on responsibility and professional ethics is not complete. In the field of law, technical skills that ignore aspects relating to the responsibilities entrusted to him and his profession in general, as well as ethical values and measurements that must serve as guidelines in carrying out his profession.